(untitled) (Research, Society and Development, 2021)
Violence is considered a serious social and public health problem, which can take physical, sexual, psychological forms or appear in the form of neglect. Coping with neglect against children requires understanding its meaning in the various life contexts, including education. The objective of this work was to understand the meanings of child neglect for educators of public and private schools. A qualitative research was conducted in a public school and three private individuals using semi-structured interviews with fourteen teachers. In content analysis, data were organized into the following categories: 1) conceptions of negligence; 2) aggressors and localities; 3) signs of negligence; 4) consequences and differences in the neglect of students from public and private schools. The importance of formative actions to identify, prevent and assist victims is highlighted. In this process, the health professional becomes indispensable to act as articulator of the protection network in intersectoral actions through health education.